(untitled) (International Journal of Engineering and Computer Science, 2014)
Today’s Online Social Networks (OSNs) do not provide an ability to control the contents of the message posted on user’s private wall. Any unwanted contents can be easily posted on the walls. Security in posting of unwanted message is an important issue in OSN. Up to now OSN have provided little control regarding who can post on user’s private wall. Here we have proposed a system that will prevent unwanted messages from being posted on user’s wall. To achieve this, the messages are scanned using text categorization techniques. We have also proposed a Blacklisting mechanism which will block such frequent message creators and prevent them from further posting any messages on the user’s wall.